Superpower Dominance: The Yum Kippur Case - Soueidan, Mohamad Hasan (Technium Social Sciences Journal, 2021)
The Yum Kippur War, or as the Egyptians call it The October War, is one of the most important wars in the history of the Middle East between the coalition of Egypt and Syria versus Israel. It occurred at a time when the two superpowers then, the Americans and the Soviet Union, were in engaging in what was called the Cold War. For that every Superpower used to support a certain party of conflict to assure the balance of global dominance isn’t affected. This paper reviews American foreign policy during the war in 1973. It concentrates on how the American institutions and foreign policy activists acted and influenced the outcome of the war. The paper finally conducts a counter analysis on what could have happened if the Americans didn’t support the Israelis in the war.